Materials Development of Reading and Writing by Using Digital Media for Students of Tenth Grade - Raden Rara Evi Oktaviani Sandhi; Nurhaedah Gailea; Akhmad Baihaqi (Hasanuddin University, 2025)
Mastering a language takes time and process. To help students learn English, preparing teaching materials is one of the important parts in the process of learning. This research focuses on developing reading and writing materials because many students have difficulty to broaden their vocabulary and how to deliver the ideas into writing. Furthermore, this research aims to find out target needs, to analyze learning needs, and to discuss the effectiveness of the teaching materials to improve students’ reading and writing skills. SMKN 5 Kota Serang was selected as the location of the research with 34 students in the 10th grade. Then, the method used was research and development by applying the ADDIE model. The questionnaires distributed were to observe needs analysis and the expert judgement. The data of needs analysis helped in developing the teaching materials, while the data of the expert judgement were used to evaluate the appropriateness of the developed materials. From the results, the developed narrative texts materials were categorized as “good” with an average score of 3.24, and the developed procedure texts materials were categorized as “very good” with an average score of 3.46. In conclusion, the developed materials are appropriate and can be used for the 10th-grade students at the school. Keywords: Materials Development, Reading and Writing